Risk factors for cefotaxime resistance in children with pneumonia - Anak Agung Made Sucipta; Ida Bagus Subanada; Samik Wahab (Indonesian Pediatric Society Publishing House, 2012)
Background Pneumonia is a health problem in developing countries, often caused by bacterial agents. The 'Widespread use of cefotaxime, a third􀁒generation of cephalosporin, may lead to increased incidence of resistance to this antibiotic. Several studies have reported on risk factors associated v.ith resistance to cefotaxime. Objective To identify risk factors for cefotaxime resistance in children 'With pneumonia. Methods We performed a case􀁒control study at Sanglah Hospital between January 2006􀁒December 2010. The case group included children with blood culture􀁒positive pneumonia and resistance to cefotaxime by sensitivity test. The control group was selected from the same population as the case group, but the bacteria isolated from these subjects were sensitive to cefotaxime. We tested the folloMng risk factors for resistance to cefotaxime: age :53 years, microorganism species, history of antimicrobial use, and history of hospitalization within the prior 3 months. Chi square test and logistic regression analysis were performed to determine any associations between the four potential risk factors and resistance to cefotaxime. A P<0.05 was considered to be statistically significant. Results Univariate analysis showed that the risk factors for resistance to cefotaxime were history of antimicrobial use in the prior 3 months (OR 2.79; 95%CI 1.40 to 5.55; P􀁓O.OOI) and history of hospitalization Mthin the prior 3 months (OR 5.57; 95%CI 1.95 to 15.87; P=<O.OOOl). By multivariate analysis, risk factors associated Mth resistance to cefotaxime were history of antimicrobial use in the prior 3 months (OR 2.4; 95%CI 1.18 to 4.86; P=0.015), history of hospitalization within the prior 3 months (OR 4.7; 95%CI 1.62 to 13.85; P􀁓0.004), and history of breast feeding for less than 2 months (OR 2.3; 95%CI 1.0 to 5.4; P􀁓0.042). Conclusion History of antimicrobial use and history of hospitalization within the prior 3 monthsweresignificantrisk  factors for resistance to cefotaxime in children Mth pneumonia. [Paediatr Indanes. 2012;52:255-9].